Generation of Macrophages from Cynomolgus‐Monkey Bone Marrow as a Model to Evaluate Effects of Drugs on Innate Immunity. Issue 1 (14th April 2019) - Li, Nianyu; Ludmann, Susan A.; Anest, Lisa; He, Ching; Narayanan, Padma Kumar
Abstract: Macrophages are innate immune cells that play important roles in various physiological and pathological processes. Evaluation of pro‐inflammatory effects of drugs on macrophages has become commonplace in preclinical drug development prior to human clinical trials. Despite their body‐wide distribution, tissue macrophages are often difficult to collect from large animals and humans in a noninvasive manner. Therefore, in vitro –differentiated macrophages are important tools to facilitate cross‐species analysis of macrophage function. Although cynomolgus monkeys are an essential non‐rodent species for preclinical research, in vitro differentiation of cynomolgus‐monkey macrophages has been poorly characterized. In the present unit, we describe a protocol to differentiate cynomolgus‐monkey macrophages from isolated bone marrow mononuclear cells (BMMCs). In contrast to monocytes, cynomolgus‐monkey BMMCs show robust expansion in the presence of macrophage colony–stimulating factor in vitro, which allows expansion of many cells from a single animal donor. Macrophages differentiated from BMMCs retain many of the macrophage phenotypes and functions, including phagocytosis and cytokine release, and therefore can be used as a surrogate to assess effects of drugs on cynomolgus‐monkey macrophages. © 2019 by John Wiley & Sons, Inc.